Will be there New CO2 Emitters in the Future? Evidence of Long-run Panel Co-integration for N-11 Countries - Nasre Esfahani, Mohammad; Rasoulinezhad, Ehsan (International Journal of Energy Economics and Policy, 2016)
This article tries to explore the long-run nexus between oil consumption, GDP and carbon dioxide (CO2) emissions in the Next eleven (N-11) countries over the period 1980-2013, by using the panel c-ointegration, the panel Dynamic OLS and the panel Fully modified OLS approaches.The empirical findings indicate that there is a bidirectional long-run linkage between oil consumption – GDP per capita and oil consumption- CO2 emissions. Moreover the inverted U-shaped linkage between the square of GDP per capita and CO2 emissions, supports the existence of Environmental Kuznets Curve (EKC) hypothesis. With estimations through the panel DOLS and FMOLS, the long-run elasticity of oil consumption per capita to CO2 emissions per capita is calculated about 0.96% and positive which is in contrast to the coefficient sign of its elasticity to GDP per capita (-0.48%). Moreover, the elasticity of GDP per capita and CO2 emissions per capita to oil consumption per capita are -0.32% and 0.94%, respectively. These findings prove the negative contribution of non-renewable energy (oil) consumption per capita to GDP per capita in the N-11 group. Furthermore, due to the bidirectional long-run relationships between oil consumption and CO2 emissions, these 11 countries should find the efficient energy policies which are in line with CO2 mitigation and reaching a higher GDP per capita growth. Keywords: Oil consumption per capita, GDP per capita, CO2 emissions per capita. JEL classifications: E21, Q54, Q56